Effects of Remineralizing Agents Based on Calcium Phosphate , Sodium Phosphate, or Sodium Fluoride on Eroded Cervical Dentin - Escalante-Otarola, W. G. [UNESP]; Castro-Nunez, G. M.; Leandrim, T. P. [UNESP]; Alencar, C. M. [UNESP]; Albuquerque Jasse, F. F. de; Kuga, M. C. [UNESP] (Operative Dentistry Inc, 2021)
Objectives: To evaluate the effect of remineralizing agents on collagen matrix pattern, precipitate formation, and dentinal tubule obliteration in eroded cervical dentin. Methods and Materials: One hundred bovine cervical dentin specimens were previously eroded (0.6% hydrochloric acid, pH 2.3, 5 minutes) and then randomized into five groups (n=20): G1, control (without treatment); G2, Desensibilize Nano P (FGM); G3, MI Paste Plus (Recaldent); G4, Regenerate (NR-5); and G5, Desensibilize KF 2% (FGM). These treatments were applied in four sessions with 7-day intervals. During this period, the samples were subjected to an erosive challenge with orange juice (pH 3.8, 5 minutes). The specimens were analyzed by polarized light microscopy with picrosirius red staining, scanning electron microscopy (SEM), and energy-dispersive X-ray spectroscopy (EDX). Results: The G3 showed a higher concentration of type I collagen than G2 and G5 (p<0.05). The G3 showed greater formation of surface precipitates than that of G1 and G5 (p<0.05). In addition, G4 and G5 showed a greater number of open dentinal tubules than that of G3 (p<0.05). Conclusions: Calcium phosphate-based remineralizing agents have shown to be a promising alternative treatment for preventing deleterious effects on the eroded dentin collagen matrix. In addition, they promoted precipitate formation and dentinal tubule obliteration on the eroded dentin.